“Green” Voting and Ideology: LCV Scores and Roll-Call Voting in the U.S. Senate, 1988–1998 - Nelson, Jon P. (The Review of Economics and Statistics, 2002)
This study evaluates the roles of ideology, constituency, and political party for roll-call voting in the U.S. Senate on a broad set of environmental issues. The study estimates a model of political support using voting scores from the League of Conservation Voters (LCV) for the period 1988-1998, including observations on 91 senators for 130 roll-call votes. The study decomposes the scale-adjusted scores into relative weights due to the general electorate, the senator's support constituency, party leadership, and ideology. The main findings are that a senator's ideology is by far the most important consideration for voting profiles on environmental issues, and that party affiliation and regional loyalty explain about 74% of measured ideology. Hence, “green” voting tends to be highly partisan.